EVALUASI PELAKSANAAN PROGRAM RASKIN DIKELURAHAN MAHARATU KOTA PEKANBARU - Arief, Ibnu Sazmie; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
RASKIN program is one of the government's policy to reduce poverty in Indonesia. In the implementation of the program, based on the general guidelines issued annually RASKIN. The general guidelines of the fact the field has not fully follow the General Guidelines RASKIN. Still found a mismatch either in the process of implementation and the implementor implementing the RASKIN program. This study aims to investigate the implementation of the division of RASKIN in Pekanbaru City Village Maharatu and to identify obstacles encountered in the implementation of the RASKIN program in the Village Maharatu Pekanbaru City.In theory policy evaluation by William N. Dunn, There are six variables that form a link between policy and performance, namely: effectiveness, efficiency, adequacy, alignment, Responsiveness, and Accuracy.The method used in this research is qualitative research. With the technique done of validity of the data by triangulation, the key informant in this study. In this study, an informant who is headman of Maharatu, section head of public welfare, chairman and chief pillars of the residents of the neighborhood, as well as urban communities Pekanbaru. Then analyzes the data and manage.Based on the research and discussion that researchers do in the field, it is found that RASKIN Program Implementation in Village Maharatu not implemented to the fullest. That's because a variety of factors that affect the evaluation of these programs is difficult implemented to the fullest.Keywords: Evaluation, RASKIN Program, Village Maharatu